Mödlinger Künstlerbund 1923-1983. - Nö Dokumentationszentrum für Moderne Kunst (Mödling : Mödlinger Künstlerbund, 1983)
Heigl, Karl ; Asboth, Oscar ; Baumann, Walter ; Brenner, Harry ; Braun, Theo ; Bayer, Franz ; Brunner, Inge ; Cervenka, Kurt E. ; Derflinger, Inamaria ; Diem, Eduard ; Elsinger, Anton ; Feigl-Zellner, Johanna Margarete ; Frank-Schmidek, Günther ; Gris, Ludwig ; Kircher, Rudolf ; etc.
boek